2019
DOI: 10.1093/mnras/stz833
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Kepler non-Blazhko RR Lyrae sample: cycle-to-cyle variations and additional modes

Abstract: We analyzed the long and short cadence light curves of the Kepler non-Blazhko RRab stars. We prepared the Fourier spectra, the Fourier amplitude and phase variation functions, time-frequency representation, the O−C diagrams and their Fourier contents. Our main findings are: (i) All stars which are brighter a certain magnitude limit show significant cycle-to-cycle light curve variations. (ii) We found permanently excited additional modes for at least one third of the sample and some other stars show temporarily… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…In this paper we focused on the photometry and did not carry out a detailed analysis of the stars, except for determining the presence and occurrence rate of the Blazhko effect. We found the rate to be below 50%, contrary to the recent result of Kovács (2018), and in agreement with other studies (Jurcsik et al 2008;Prudil & Skarka 2017;Benkő et al 2019). We estimated the pe- riods of the phase and amplitude modulations and found some differences above ∼55 days modulation period, but we are limited by the length of the Campaigns.…”
Section: Discussionsupporting
confidence: 89%
“…In this paper we focused on the photometry and did not carry out a detailed analysis of the stars, except for determining the presence and occurrence rate of the Blazhko effect. We found the rate to be below 50%, contrary to the recent result of Kovács (2018), and in agreement with other studies (Jurcsik et al 2008;Prudil & Skarka 2017;Benkő et al 2019). We estimated the pe- riods of the phase and amplitude modulations and found some differences above ∼55 days modulation period, but we are limited by the length of the Campaigns.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the Kepler data demonstrated that stars where no coherent amplitude and phase variation were detected still showed irregular amplitude and phase fluctuations, similar to those seen in Cepheids (Benkő et al 2019). While over long timescales this manifests as red noise around the main harmonic series, over the much shorter TESS observations, stochastic variations can conceivably appear as a single or a few significant frequency components in some cases.…”
Section: What Is the Blazhko Effect -For An Observer?mentioning
confidence: 64%
“…Moskalik et al (2015), for example, stated that the small amplitude and phase fluctuations in the Kepler RRc stars do not resemble the classical picture of the (semi-)coherent modulations we know as the Blazhko effect. Similarly, Benkő et al (2019) found that cycleto-cycle variations in Kepler RRab stars can cause small side peaks, but the true incidence rate of quasi-periodic modulation is 51-55%. In contrast, the idea that all RR Lyrae stars are modulated was recently suggested by Kovács (2018), based on his processing of K2 data.…”
Section: What Is the Blazhko Effect -For An Observer?mentioning
confidence: 88%
“…Several resonant components, whose frequencies evolve in phase or anti-phase during the observations, show similar modulation patterns to those found between the components of the quintuplet Q 1 in KIC 3527751 (Paper I). We note that most of the FM timescales are not close to that of Kepler's orbit and its resonances which was recently reported on phase modulations in non-Blazhko RR Lyrae stars (Benkő et al 2019). However, the measured AMs, particularly in KIC 2438324, are contaminated by a systematic modulation pattern (discussed later) and by the correction of the light fraction associated to the target.…”
Section: Modulation Patternsmentioning
confidence: 52%